Controlling Protein Crystal Nucleation by Droplet‐Based Microfluidics. Issue 4 (30th December 2013) - Maeki, Masatoshi; Teshima, Yuki; Yoshizuka, Saori; Yamaguchi, Hiroshi; Yamashita, Kenichi; Miyazaki, Masaya
Abstract Herein, we demonstrate the potential of droplet‐based microfluidics for controlling protein crystallization and generating single‐protein crystals. We estimated the critical droplet size for obtaining a single crystal within a microdroplet and investigated the crystallization of four model proteins to confirm the effect of protein molecular diffusion on crystallization. A single crystal was obtained in microdroplets smaller than the critical size by using droplet‐based microfluidics. In the case of thaumatin crystallization, a single thaumatin crystal was obtained in a 200 μm droplet even with high supersaturation. In the case of ferritin crystallization, the nucleation profile of ferritin crystals had a wider distribution than the nucleation profiles of lysozyme, thaumatin, and glucose isomerase crystallization. We found that the droplet‐based microfluidic approach was able to control the nucleation of a protein by providing control over the crystallization conditions and the droplet size, and that the diffusion of protein molecules is a significant factor in controlling the nucleation of protein crystals in droplet‐based microfluidics.